2014
DOI: 10.1111/ejn.12474
|View full text |Cite
|
Sign up to set email alerts
|

Differential subcellular localization of SK3‐containing channels in the hippocampus

Abstract: Small-conductance, Ca(2+) -activated K(+) (SK) channels are expressed in the hippocampus where they regulate synaptic responses, plasticity, and learning and memory. To investigate the expression of SK3 (KCNN3) subunits, we determined the developmental profile and subcellular distribution of SK3 in the developing mouse hippocampus using western blots, immunohistochemistry and high-resolution immunoelectron microscopy. The results showed that SK3 expression increased during postnatal development, and that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
6
18
1
Order By: Relevance
“…The former studies, which did not perform any tests in KO mice for the specificity of their antibodies, showed a strong somata and dendritic labeling in rats, while using specific antibodies we found low labeling in somata but strong in the neuropil in mice. This particular neuropilar labeling pattern has been demonstrated for other ion channels in the brain (see for instance Fernández-Alacid et al, 2011; Ballesteros-Merino et al, 2012, 2014; Ferrándiz-Huertas et al, 2012) by many laboratories. Other than the antibody specificity, the reason for this discrepancy might reflect differences in the species used or in the immunohistochemical techniques employed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The former studies, which did not perform any tests in KO mice for the specificity of their antibodies, showed a strong somata and dendritic labeling in rats, while using specific antibodies we found low labeling in somata but strong in the neuropil in mice. This particular neuropilar labeling pattern has been demonstrated for other ion channels in the brain (see for instance Fernández-Alacid et al, 2011; Ballesteros-Merino et al, 2012, 2014; Ferrándiz-Huertas et al, 2012) by many laboratories. Other than the antibody specificity, the reason for this discrepancy might reflect differences in the species used or in the immunohistochemical techniques employed.…”
Section: Discussionsupporting
confidence: 59%
“…The non-uniform distribution of Cav3.1 and Cav3.2 shown here seems to be cell type-dependent, as Cav3.1 showed a uniform distribution in relay neurons of the thalamic dorsal lateral geniculate nucleus (Parajuli et al, 2010). Non-uniform distribution patterns has been previously described for different ion channels, including Cav2.3, GIRK and SK channels (Fernández-Alacid et al, 2011; Ballesteros-Merino et al, 2012, 2014; Parajuli et al, 2012). …”
Section: Discussionmentioning
confidence: 81%
“…For instance, one study has suggested that K Ca 2 channels might be present on the AIS on the basis of increased neuronal excitability that was observed after block of axonal P/Q‐ and N‐type calcium channels (15). More recently, a study demonstrated that K Ca 2 channels are present in the synaptic terminals of CA1 pyramidal neurons (14). At the cellular level, different K Ca 2 channel subtypes occupy different subcompartments in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In most neurons, K Ca 2 channels are typically found on dendrites and at much lower levels on the soma (6, 11, 13). Although some reports have suggested that KCa2 channels might be found in the axon (14)—and the axon initial segment (AIS), in particular (15)—this has yet to be definitively established.…”
mentioning
confidence: 99%
See 1 more Smart Citation